The Role Of Cation And Anion Exchange Resin For The Removal Of Cod, Colour, And Nh3-n From Coffee Processing Wastewater - Emmanuel, Madu Ijanu (2021)
Coffee is the second most traded commodity after petroleum. The cultivation and production of coffee have expanded globally. However, the processing of coffee from coffee bean to drink requires a large quantity of clean water and results in a considerable volume of contaminated wastewater. The physicochemical properties analyses of coffee wastewater reveal that the coffee processing wastewater is dark brown because it contains several non-biodegradable and suspended colloidal organic particles. Therefore, it urges to treat the coffee processing wastewater before discharge into the nearest watercourse. Over the years, various technologies have been implemented to treat the coffee wastewater to mitigate standard discharge limits set by Environmental agencies. In the present study, the influence of cation and anion exchange resins was determined to remove COD, colour, and NH3-N from coffee wastewater. The experiments were conducted with varying pH, resin doses, reaction time, shaking speed and temperature. Kinetics, thermodynamics and surface modelling were employed to determine the ion-exchange resin behaviour in removing COD, colour and NH3-N from coffee wastewater. Response surface methodology (RSM) was utilized to optimize the ion exchanges experimental conditions on maximum removal of COD, colour and NH3-N from coffee wastewater. Besides, the removal of COD, colour and NH3-N from coffee wastewater using cation and anion exchange resins was conducted using an up-flow column system. Finally, the regeneration of cation and anion exchange resins were also carried out.